The idea of a university - Newman, John Henry, Saint, 1801-1890 (Yale University Press, 1996)
This edition of The idea of a University includes the full text of the original 1852 publication and four selections from the subsequently added "University Subjects" together with five essays by leading scholars that explore the background and the present-day relevance of Newman's themes
Keywords: Newman, John Henry, -- Saint, -- 1801-1890. -- Idea of a university.; Idea of a university (Newman, John Henry, Saint); Newman, John Henry -- 1801-1890 -- The idea of a university defined; Newman, John Henry. -- (The) idea of a university defined.; Education, Higher -- Philosophy.; Universities and colleges -- Philosophy.; Universities and colleges.; Universities; Enseignement supérieur -- Philosophie.; Universités -- Philosophie.; Universités.; universities (institutions); colleges (institutions); EDUCATION -- Higher.; Universities and colleges; Education, Higher -- Philosophy; Universities and colleges -- Philosophy; Hochschule; Universiteiten.; Doelstellingen.